Making sense of astrocytic calcium signals: from acquisition to interpretation - Semyanov, Alexey; Henneberger, Christian; Agarwal, Amit (Nature reviews. Neuroscience, 2020)
Astrocytes functionally interact with neurons and with other brain cells. Although not electrically excitable, astrocytes display a complex repertoire of intracellular Ca2+ signalling that evolves in space and time within single astrocytes and across astrocytic networks. Decoding the physiological meaning of these dynamic changes in astrocytic Ca2+ activity has remained a major challenge. This Review describes experimental preparations and methods for recording and studying Ca2+ activity in astrocytes, focusing on the analysis of Ca2+ signalling events in single astrocytes and in astrocytic networks. The limitations of existing experimental approaches and ongoing technical and conceptual challenges in the interpretation of astrocytic Ca2+ events and their spatio-temporal patterns are also discussed.
Online publiziert: 1. September 2020
Gesehen am 05.01.2026